Students Responses to the Hannafin and Peck Learning Media Worksheet in Islamic Religious Education Subject - Mulyawan Safwandy Nugraha; Yusuf Pardamean Syarif; Ujang Dedih (KEDJATI Journal of Islamic Civilization, 2024)
Teaching and learning activities must use motivation as a driving force for student absorption because students can obtain information from the programmed curriculum to increase the quality of learning. This research aims to analyze and describe students' responses to the Hannafin and Peck learning media worksheet in Islamic religious education (PAI) subjects in class 5 of Islamic elementary school. This study used a quantitative approach with a descriptive analysis. The participants were 20 students. The data collection technique was in the form of a statement questionnaire. The results showed that the average student response to the Hannafin and Peck learning model was 85% with a good category, the response to the PAI lesson was 75% with enough category, and the response to the learning process was 80% with a good category. Hence, the total average of students' responses was 80% with a good category. Thus, the Hannafin and Peck learning model in PAI subjects could be implemented at school. Also, it is hoped that there will be more in-depth research regarding the Hannafin and Pack learning model.